(untitled) (Journal of Universal Science Research, 2024)
The scientific review article presents a comprehensive analysis of allergic rhinosinusitis (ARS) in the context of pregnancy, considering the features of diagnosis, clinical presentation, therapy and prevention. Introduces the issue of ARS in pregnant women, highlighting the relevance of the topic in the light of physiological changes in the body of expectant mothers. The following highlights the features of diagnosing ARS, paying attention to the safety of the procedures performed for the mother and fetus. The emphasis is on hormonal changes and their association with worsening symptoms of ARS during pregnancy. The role of drug therapy and the need for a personalized approach to the selection of drugs are emphasized. Sections are presented on the effects of treatment on fetal development, including assessment of drug safety and the possible consequences of insufficient treatment. In the context of prevention, measures to prevent the development of ARS and the role of allergen-specific immunotherapy are discussed.